Effects of High-Intensity Ultrasound-Assisted Extraction Duration on the Quality of Monopterus albus Bone Broth - LIAO E, LIU Na, LI Han, ZHANG Ying, YANG Qian, CHEN Jiwang (Shipin Kexue)
To investigate the effects of varying durations of high-intensity ultrasound-assisted extraction on the quality of Monopterus albus bone broth, the fish bone broth, prepared at atmospheric pressure, was subjected to low-frequency and high-intensity ultrasound (power 360 W, and frequency 20 kHz) treatment for 0, 1, 2, 3, 4, 5, and 6 min. Subsequently, color, microscopic distribution, zeta potential, particle size, water-soluble protein, soluble solids, and mineral contents (e.g., Mg, K, Ca, and Na) were measured. Results indicated that as ultrasonic treatment time increased, the absolute value of the ζ-potential first rose (up to 9.28 mV) and then declined (to 7.39 mV) (P 0.05). Compared with those before treatment, the contents of Mg, K, Ca, and Na increased by 10.20%, 37.18%, 5.82%, and 28.75%, respectively, after 4 min of treatment. Electronic tongue analysis indicated that the response values for bitter taste and aftertaste initially increased and then decreased, reaching peak values of 8.56 and 1.53 at 1 min of ultrasonic treatment, respectively. Additionally, the response values for bitter taste and bitter aftertaste were reduced at durations equal to or more than 3 min. Gas chromatography-ion mobility spectrometry (GC-IMS) analysis demonstrated that ultrasonic treatment significantly enhanced the concentrations of fruity, oily, meaty, and nutty flavor compounds (e.g., methyl heptanoate, butyl butyrate, β-cyclocitral, n-octanal, 2-methoxy-3-sec-butylpyrazine, and 2-ethyl-5-methylpyrazine), while effectively reducing the concentrations of pungent odor substances such as hexanal and butyric acid. The sensory score of the fish bone broth was the highest at 4 minutes of ultrasound treatment. In conclusion, high-intensity ultrasonic treatment can significantly improve the quality of M. albus bone broth, providing a theoretical foundation for its efficient and high-quality processing.